(untitled) (Management and Connections Journal, 2025)
Companies from different sectors are increasing the use of social themes on their brand communication efforts. The LGBTQIAPN+ cause is upon other social causes that is being used to demonstrate support and organizational efforts to bring about a more inclusive society. Although this has become practice, little is known about their real benefits, or even, how adequate are these advertisements used by these companies. Aiming to provide empirical evidence for these questions, an experimental study with 120 participants from generation Z, was conducted. The study analyzed the effect of an advertisement demonstrating the engagement of a company with the LGBTQIAPN+ cause (higher x lower) over attitude towards the ad, the brand and buying intention. Results suggest the higher the engagement’s perception, the higher will be attitude towards the ad, the brand and buying intention and, these effects are moderated by political positioning and levels of social cause support of participants.